2020
DOI: 10.1007/s11207-020-01688-y
|View full text |Cite
|
Sign up to set email alerts
|

How Good Is the Bipolar Approximation of Active Regions for Surface Flux Transport?

Abstract: We investigate how representing active regions with bipolar magnetic regions (BMRs) affects the end-of-cycle polar field predicted by the surface flux transport model. Our study is based on a new database of BMRs derived from the SDO/HMI active region patch data between 2010 and 2020. An automated code is developed for fitting each active region patch with a BMR, matching both the magnetic flux and axial dipole moment of the region and removing repeat observations of the same region. By comparing the predicted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…The database is clearly not ideal for this purpose. The BMR databases compiled more recently by Yeates et al (2007) and by Yeates (2020), although of excellent quality, are not suitable either as they tabulate the physical properties of each BMR at the time it crosses the central meridian, not when it newly emerges.…”
Section: Comparison Tomentioning
confidence: 99%
See 1 more Smart Citation
“…The database is clearly not ideal for this purpose. The BMR databases compiled more recently by Yeates et al (2007) and by Yeates (2020), although of excellent quality, are not suitable either as they tabulate the physical properties of each BMR at the time it crosses the central meridian, not when it newly emerges.…”
Section: Comparison Tomentioning
confidence: 99%
“…Otherwise, SFTMs usually make use of solar magnetograms (e.g. Whitbread et al 2018;Virtanen et al 2018;Yeates 2020) or Ca II K spectroheliograms (e.g. Virtanen et al 2019) instead.…”
Section: Introductionmentioning
confidence: 99%
“…We adopt a symmetric solar bipole model (Yeates 2020) that can be scaled to represent larger starspots. The centroids of the positive and negative polarities are placed at (𝑠 + , 𝜙 + ) and (𝑠 − , 𝜙 − ), respectively.…”
Section: Bipole Modelmentioning
confidence: 99%
“…The random convective motions can be treated as a diffusion process (Leighton 1964), which can be implemented in surface flux transport models (SFTMs) as a random walk. Estimates of the diffusion rate D from observations typically indicate D = 250 km 2 s −1 (Jafarzadeh et al 2014), but higher values up to D = 500 km 2 s −1 have also been reported (Wang et al 2002;Yeates 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion of the inflows into global SFTMs improve the match to the global dipole for the solar cycles 13 to 21 (Cameron & Schüssler 2012), and can account for the excess strength of the polar field at activity minimum in simulations, by effectively reducing the tilt angle of active regions (Cameron et al 2010;Yeates 2014). However, recently Yeates (2020) argued that this excess strength can be a result of the bipolar approximation of the active regions. On the other hand, Yeates (2014) found that the incorporation of the inflows (in form of a perturbation of the meridional flow) delays the dipole reversal times for solar cycle 23 with respect to the observed cycle.…”
Section: Introductionmentioning
confidence: 99%